Qualidade fisiológica de sementes de Senna multijuga de diferentes procedências do estado de São Paulo - Flávio, João José Prieto [UNESP] (2014)
Senna multijuga (Rich.) H. S. Irwin and Barneby have been widely used for reforestation with great potential for adaptation in different environments. The present research aimed to evaluate the physiological quality of Senna multijuga seeds from different locations in São Paulo State through seed germination and vigor tests. Nine lots were formed with seeds from the cities of Promissão, Ribeirão Grande, Capão Bonito, Pradópolis, Altinópolis, Luiz Antônio, Batatais and Guatapará. The germination test was conducted at 25, 30, 35 and 25- 35 °C with seeds of each lot scarified with sulfuric acid for 10, 15 and 20 minutes. The accelerated aging test was conducted with seeds of each lot by the traditional method and saturated NaCl solution for 96 hours at 45 ºC. In the electrical conductivity test, 30 and 60 seeds of each lot were soaked in 75 mL of water at 25 °C for 2, 4, 6, 12, 18 and 24 hours. The leaching test of K+ and Na+ was conducted with 30 and 60 seeds of each lot soaked for 24 hours at 25° C. Data were subjected to variance analysis and means were compared by Tukey test at 5% probability. There are small differences between the germination of seeds from lots of different places of São Paulo State. The germination test can be carried out at 25 °C with scarified seeds with sulfuric acid for 15 minutes. The traditional accelerated aging test at 45 °C for 96 hours is effective in promoting changes in seeds germination. The accelerated aging test with saturated NaCl solution conducted at 45 °C for 96 hours, the electrical conductivity test carried out at 25 °C with 30 and 60 seeds soaked in 75 mL of water for periods of 2, 4, 6, 12, 18 and 24 hours and leaching test of K+ and Na+ performed with 30 and 60 seeds soaked in 75 mL of water for 24 hours at 25 °C are not effective to discriminate seed lots of the physiological quality